Nuevos retos para la PsicologÌa Social: edadismoy perspectiva de gÈnero - De Lemus, Soledad (2010)
Population aging is a current demographic phenomena produced by a constant decrease in birthrate and an increase of life expectancy . This process is expected to keep on expanding and consolidating globally , both in developed and developing countries. Age is a social construct, a period of life which is dif ferently defined in several cultures, although it always shares some features. Quality of life related to age is strongly af fected by socially accepted attitudes mi beliefs toward this background variable. Demographic research also shows a clear feminization of aging caused by womení s greater longevity Thus, it is an important challenge for Social Psychology in the XXI century to recognize investigate and prove how the combination of these two social categories -age md gender - and the social processes related to them inhibit or facilitate the integration of these people in the society where they live.